Proliferative verrucous leukoplakia misdiagnosed as oral leukoplakia - Rajesh Kumar Gupta; Nidhi Rani; Bharat Joshi (Wolters Kluwer Medknow Publications, 2017)
Correct diagnosis of white lesions of the oral cavity is sometimes difficult, because some oral white lesions behave differently and tend to change their appearance with time. Clinicians often wrongly diagnose such lesions as oral leukoplakias and treat simply. Lesions recur and turn malignant. Proliferative verrucous leukoplakia (PVL) is a distinct form of oral leukoplakia characterized by a high recurrence rate and high rate of transformation into oral squamous cell carcinoma. We present herein a case of PVL which was misdiagnosed as oral leukoplakia and progressed to oral carcinoma.